2008
DOI: 10.1158/1078-0432.ccr-08-0212
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Vascular Maturation and Improved Drug Delivery Induced by Methylselenocysteine Leads to Therapeutic Synergy with Anticancer Drugs

Abstract: Purpose: Our previously reported therapeutic synergy between naturally occurring selenoamino acid methylselenocysteine (MSC) and anticancer drugs could not be shown in vitro. Studies were carried out to investigate the potential role of MSC-induced tumor vascular maturation and increased drug delivery in the observed therapeutic synergy in vivo. Experimental Design: Mice bearing s.c. FaDu human head and neck squamous cell carcinoma xenografts were treated with MSC (0.2 mg/d  14 days orally). Changes in microv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(92 citation statements)
references
References 25 publications
(49 reference statements)
4
87
0
1
Order By: Relevance
“…As discussed below, many studies testing the effects of antiangiogenic drugs have shown a presence of a "normalization window"-a time period beginning with the appearance of a normalized vascular phenotype (typically within 1 -2 days of starting treatment), and ending when features of normalization are lost Winkler et al 2004;Jain 2005b;Batchelor et al 2007;Kamoun et al 2009 Xian et al 2006;McCarty et al 2007;Mazzone et al 2009. c This is controversial given recent reports of increased metastasis after antiangiogenic therapy in certain animal models (Ebos et al 2009;Paez-Ribes et al 2009 Gorski et al 1999;Hansen-Algenstaedt et al 2000;Lee et al 2000;Kozin et al 2001;Ader et al 2003;Winkler et al 2004;Ansiaux et al 2005Ansiaux et al , 2006Pore et al 2006a;Dings et al 2007;Kashiwagi et al 2008;Batra et al 2009;Cerniglia et al 2009;Tsukada et al 2009;McGee et al 2010. g Teicher et al 1995a,b;Wildiers et al 2003;Segers et al 2006;Dickson et al 2007a,b,c;Bhattacharya et al 2008Bhattacharya et al , 2009Zhou et al 2008;Juan et al 2009;Zhou and Gallo 2009;J Liu, S Liao, B Diop-Frimpong, et al, unpubl. data. section, we discuss the key molecules implicated in tumor vessel biology with a focus on their role in regulating vascular normalization.…”
Section: Evidence For Vascular Normalization In Tumors Preclinical Evmentioning
confidence: 99%
See 2 more Smart Citations
“…As discussed below, many studies testing the effects of antiangiogenic drugs have shown a presence of a "normalization window"-a time period beginning with the appearance of a normalized vascular phenotype (typically within 1 -2 days of starting treatment), and ending when features of normalization are lost Winkler et al 2004;Jain 2005b;Batchelor et al 2007;Kamoun et al 2009 Xian et al 2006;McCarty et al 2007;Mazzone et al 2009. c This is controversial given recent reports of increased metastasis after antiangiogenic therapy in certain animal models (Ebos et al 2009;Paez-Ribes et al 2009 Gorski et al 1999;Hansen-Algenstaedt et al 2000;Lee et al 2000;Kozin et al 2001;Ader et al 2003;Winkler et al 2004;Ansiaux et al 2005Ansiaux et al , 2006Pore et al 2006a;Dings et al 2007;Kashiwagi et al 2008;Batra et al 2009;Cerniglia et al 2009;Tsukada et al 2009;McGee et al 2010. g Teicher et al 1995a,b;Wildiers et al 2003;Segers et al 2006;Dickson et al 2007a,b,c;Bhattacharya et al 2008Bhattacharya et al , 2009Zhou et al 2008;Juan et al 2009;Zhou and Gallo 2009;J Liu, S Liao, B Diop-Frimpong, et al, unpubl. data. section, we discuss the key molecules implicated in tumor vessel biology with a focus on their role in regulating vascular normalization.…”
Section: Evidence For Vascular Normalization In Tumors Preclinical Evmentioning
confidence: 99%
“…j Teicher et al 1995bJain et al 1998;Bernsen et al 1999;Cohen-Jonathan et al 2001;Delmas et al 2003;Ansiaux et al 2005Ansiaux et al , 2006Pore et al 2006b;Segers et al 2006;Cerniglia et al 2009;Qayum et al 2009;Cham et al 2010. k Ader et al 2003;Hamzah et al 2008;Kashiwagi et al 2008;Stockmann et al 2008;Maione et al 2009;Mazzone et al 2009;Skuli et al 2009;Tsukada et al 2009;Rolny et al 2011. l Yuan et al 1996Lee et al 2000;Wildiers et al 2003;Tong et al 2004;Nakahara et al 2006;Dickson et al 2007b;Kurozumi et al 2007;Taguchi et al 2008;Zhou et al 2008;Kamoun et al 2009;Ohta et al 2009;Gallo 2009. m Jain et al 1998;Izumi et al 2002;Ansiaux et al 2005;Salnikov et al 2005;Bhattacharya et al 2008Bhattacharya et al , 2009Schnell et al 2008;Cerniglia et al 2009. n Dickson et al 2007c;Kashiwagi et al 2008;di Tomaso et al 2009;…”
Section: Vegfunclassified
See 1 more Smart Citation
“…Insufficient perivascular cell coverage has been attributed to the increased microvascular permeability in and around the tumor (20,21). We investigated whether the tumor K transOX63 values correlate with the immunostaining of ␣-smooth muscle actin (␣SMA), a marker of pericytes.…”
Section: Lack Of Perivascular Cell Coverage May Be Responsible For Inmentioning
confidence: 99%
“…Uptake of autofluorescent doxorubicin drug was also measured by fluorescent microscopy in s.c. leukemia xenografts at 1 to 24 hours following doxorubicin injection. Frozen tumors were cut into approximately 5-to 10-μm-thick sections and evaluated for fluorescent tissue intensity in an average of three maximum intensity projection images with a resolution of 0.23 μm under a ×63 objective lens of Leica confocal microscope as previously described (31). Images were obtained and digitized under identical acquisition variables.…”
Section: Determination Of Doxorubicin Levelsmentioning
confidence: 99%